Fluorinated polymers. Volume 1, - Améduri, B.; Sawada, Hideo (Royal Society of Chemistry, 2017)
Fluorinated Polymers: Applications covers the uses of the different materials.
Keywords: Fluoropolymers.; elektronické knihy; electronic books